2015
DOI: 10.1063/1.4913207
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and motion behaviors of water droplet on graphene under thermal-electric coupling field

Abstract: Articles you may be interested inLinear relationship between water wetting behavior and microscopic interactions of super-hydrophilic surfaces Ab initio and classical molecular dynamics studies of the structural and dynamical behavior of water near a hydrophobic graphene sheet J. Chem. Phys. 138, 204702 (2013); 10.1063/1.4804300Droplet contact angle behavior on a hybrid surface with hydrophobic and hydrophilic properties A study on the dynamic behaviors of water droplets impacting nanostructured surfaces Wetti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Recent experimental work has shown that the assumed hydrophobicity of graphitic surfaces is the result of hydrocarbon contaminants and that clean graphitic surfaces are actually mildly hydrophilic. The widespread results for the contact angle of water on the surface obtained from simulations using force field methods has provoked studies of the water–graphene interaction potential using electronic structure calculations. These studies can be divided into two classes, namely, those carried out on the “infinite” system using a supercell replicated through periodic boundary conditions and those involving a sequence of H 2 O– cluster models followed by extrapolation to the graphene limit. Due to the challenges of accurately describing the various contributions to the binding energy and in properly extrapolating long-range interactions, these calculations have resulted in a considerable spread in the values of the binding energy.…”
mentioning
confidence: 99%
“…Recent experimental work has shown that the assumed hydrophobicity of graphitic surfaces is the result of hydrocarbon contaminants and that clean graphitic surfaces are actually mildly hydrophilic. The widespread results for the contact angle of water on the surface obtained from simulations using force field methods has provoked studies of the water–graphene interaction potential using electronic structure calculations. These studies can be divided into two classes, namely, those carried out on the “infinite” system using a supercell replicated through periodic boundary conditions and those involving a sequence of H 2 O– cluster models followed by extrapolation to the graphene limit. Due to the challenges of accurately describing the various contributions to the binding energy and in properly extrapolating long-range interactions, these calculations have resulted in a considerable spread in the values of the binding energy.…”
mentioning
confidence: 99%
“…Sophisticated control of wetting is possible by coupling electrical and thermal effects. MD simulations indicate that increasing the temperature results in a linear reduction in the WCA that can then be reversed by increasing the charge magnitude, enabling a hydrophilic to hydrophobic transition 36 .…”
Section: Extrinsic Tuning Of the Wettability Of 2d Materialsmentioning
confidence: 99%
“…However, the wettability of the monolayer graphene is quite dependent on its substrate, implying that the monolayer graphene is of wetting transparency, and the number of layers is an important parameter for the wettability of graphene . Regarding the fluid–graphene system, the previous efforts were mainly devoted to the static and dynamic wettability, the driving and fast diffusion of water droplets, the liquid–graphene interfacial friction, and the fluid boundary slip confined in the graphene channel, and so forth. Recently, however, it was demonstrated experimentally that the monolayer graphene, as a coating of the nanochannel, can significantly increase the boundary slip of the confined fluid. It was found that the slip length of the fluid is explicitly sensitive to the substrate of the monolayer graphene.…”
Section: Introductionmentioning
confidence: 99%